Associations of muscular and cardiorespiratory fitness with total and central body fat in adolescents: The HELENA Study. Issue 2 (19th August 2009) - Moliner-Urdiales, D; Ruiz, J R; Vicente-Rodriguez, G; Ortega, F B; Rey-Lopez, J P; España-Romero, V; Casajús, J A; Molnar, D; Widhalm, K; Dallongeville, J; González-Gross, M; Castillo, M J; et al.
Abstract : Objective: To examine the association of healthrelated physical fitness with total and central body fat in adolescents. Participants/Methods: The present cross-sectional study comprises 363 Spanish adolescents (186 female participants) aged 12.5–17.5 years. We assessed fitness by the 20-m shuttle run test (cardiorespiratory fitness); the handgrip strength, the standing broad jump and the Abalakov tests (muscular strength); and the 4×10-m shuttle run test (speed–agility). Total body fat was measured by dual energy x-ray absorptiometry (DXA), BodPod and sum of six skinfolds, and central body fat was measured by DXA at three regions (R1, R2 and R3) and waist circumference. Results: The Abalakov, the standing broad jump, the 4×10-m shuttle run and the 20-m shuttle run tests were negatively associated with all markers of total and central body fat in men and women after controlling for age, pubertal status and objectively assessed physical activity (p<0.01). Handgrip strength test was positively associated with waist circumference (p<0.01). Conclusions: Lower body muscular strength and cardiorespiratory fitness are negatively and consistently associated with total and central body fat in adolescents, whereas levels of upper body muscular strength were superior in adolescents with higher levels of central body fat.